Green Collaboration: Mewujudkan Gaya Hidup Berkelanjutan di Kelurahan Poris Gaga Kota Tangerang - Faedurrohman Faedurrohman; Muhammad ‘Ainul Yaqin (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2024)
The community service that has been carried out by lecturers and students of the University of Muhammadiyah Tangerang in Poris Gaga Village, Batuceper District, Tangerang City with the theme "Green Collaboration for Sustainable Living," aims to increase public awareness of the importance of environmental preservation and empowerment. This activity involves various programs designed to increase awareness of the sustainable environment, such as tutoring and reciting with environmental education, mutual service work, planting herbal plants for live pharmacies, waste banks, and digitalization seminars for MSMEs with a focus on environmentally friendly packaging. This collaboration program has succeeded in integrating sustainability aspects into various sectors of people's lives, building collective awareness of the importance of environmental conservation, and encouraging active community participation in protecting their environment. The impact of this activity is felt positively by the community, especially in increasing knowledge, awareness, and community participation in the importance of a sustainable lifestyle. Keywords: Green Collaboration, Sustainable Living, Environmental Awareness